Menelisik Peran Keunggulan Produk dan Pengalaman Pengguna: dalam Perspektif Theory Of Planned Behavior - Seftarina Azzahra; Roymon Panjaitan; Amron Amron; Haunan Damar (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study investigates the impact of augmented reality (AR), product superiority, and user experience on consumer satisfaction, focusing on the use of L’Oréal cosmetics’ Virtual Try-On feature within an e-commerce platform. It delves deeply into how these three factors influence satisfaction both directly and through mediating effects, drawing on the Theory of Planned Behavior (TPB) and the Theory of Reasoned Action (TRA) to provide a comprehensive perspective on consumer behavior in interactive, technology-driven shopping environments. A quantitative methodology was employed, surveying 100 respondents who have experienced L’Oréal’s AR feature. The data were analyzed using SEM-PLS to construct and empirically validate a structural model of the relationships among the constructs. The results demonstrate that AR significantly enhances consumer satisfaction, both directly and indirectly via product superiority and user experience, each serving as key mediators. Additionally, the study’s theoretical foundation highlights that contemporary consumer technology adoption is shaped by perceived usefulness, convenience, and experiential value during digital interactions, reinforcing the model’s relevance for understanding the factors driving consumer satisfaction with AR technologies.